Intraoral lipoma: Review of literature and case report - Mahendra Raj; Thanuja Ramadoss; G Anuradha; Shobana Devi (Wolters Kluwer Medknow Publications, 2012)
Lipomas are benign mesenchymal neoplasms of soft tissue that can be found in any part of the human body. Conversely, their presence in the oral mucosa is rather uncommon, with approximately 4% of the cases occurring in the oral cavity. The aim of this paper is to present the importance of diagnosis and treatment of intraoral lipoma. Clinicians must be able to recognize rare lesions, like intraoral lipomas, to provide appropriate treatment, thereby ensuring comfort and quality of life for the patient.